Tax Compliance Actions by Tax Authorities and Voluntary Compliance with Tax Obligations by Individual Taxpayers - Bezerra, Thales Vinícius Santiago; Oliveira, Oderlene Vieira de; Souza, Lucas Lopes Ferreira de (Advances in Scientific and Applied Accounting, 2024)
Research objective: Tax compliance actions aim to improve the relationship between the tax authorities and taxpayers, increasing voluntary compliance with tax obligations and reducing administrative and judicial litigation. In this sense, the defined objective was to analyze whether tax compliance actions increase voluntary compliance with tax obligations. Methodology: Thus, a quantitative approach was used, through analysis of latent classes, carried out on the baseed on longitudinal data from the Federal Revenue, with 531 individual taxpayers, related to compliance action. Results: After the action, it was found that the taxes owed had a statistically significant increase and the tax gap was increasingly reduced between 2015 and 2018, indicating that the implemented tax compliance actions were effective in promoting voluntary compliance with tax obligations by taxpayers. In addition, the action also presented advantages to taxpayers, since, when there is a spontaneous regularization, there is less possibility of facing a tax procedure, as well as a reduction in administrative costs and the amount of litigation. Practical and theoretical contributions: The practical contributions are aimed at enhancing future tax compliance initiatives carried out by Federated Entities. Furthermore, the theoretical contribution utilizes the Slippery Slope Model, which illustrates an upsurge in voluntary compliance with tax obligations following a compliance action, attributed to heightened authority and confidence in the tax regulatory body. As a result, this theoretical contribution underscores the significance of the Slippery Slope Model in comprehending taxpayer behavior and in devising more efficient tax compliance strategies.